Charismatic Economies: Pentecostalism, Economic Restructuring, and Social Reproduction - Barker, Isabelle V. (New Political Science, 2007)
Pentecostalism is one of the world's fastest growing religions, expanding most quickly in Latin America, sub-Saharan Africa, and parts of Asia. To make sense of this expansion in so many developing regions, I suggest that Pentecostalism fosters norms and behaviors that harmonize with neoliberal economic restructuring. I frame this theoretically with Polanyi's notion of double movement. In our current era of weakened state governance vis-à-vis neoliberal trade and fiscal policy, non-state sites of reaction have emerged. Pentecostalism is one such site, and, in contrast with Polanyi's example, I suggest that Pentecostalism has embedded the self-regulated aspects of neoliberal capitalism. I make this argument by using the feminist political economy theorization of social reproduction to interpret a number of empirical studies of Pentecostalism. Pentecostalism addresses dilemmas of social reproduction engendered by neoliberalism, and so may be said to embed this form of economic organization in human social life in a way that reinforces neoliberal capitalism.
Keywords: Pentecostalism; capitalism; double movement; economic systems; economics; neoliberalism; social interaction; social reproduction; social structure; socialization

The Poverty of the Global Order - Da Costa, Dia; Mcmichael, Philip (Globalizations, 2007)
This paper argues that the legitimacy of the global order depends not on economic progress alone, but on the progressive naturalization of its epistemological foundations, through 'new solutions' to old problems by states and development agencies. New solutions become methods of social control through which the dominant visions of what count as viable futures are reproduced. We critique efforts to humanize development (e.g., by the World Bank, Amartya Sen) as evidence of development's epistemological crisis. Deploying Karl Polanyi's distinction between formal and substantive economy, we consider examples of substantive economy, which realize equality through strategic sovereignty and representational power, in collective and individual terms. These represent practical and epistemological 'spaces of hope' for critique of the crisis of the market epistemology that infects development studies and international relations. Este documento sostiene que la legitimidad del orden global no depende solamente del progreso económico, sino de la naturalización progresiva de sus fundamentos epistemológicos, a través de 'nuevas soluciones' a problemas antiguos mediante estados y agencias del desarrollo. Las nuevas soluciones se convierten en métodos de control social, a través de los cuales se reproducen las visiones dominantes de lo que cuenta como futuros viables. Criticamos los esfuerzos de humanizar al desarrollo (p.e. Banco Mundial, Amartya Sen) como evidencia de la crisis del desarrollo epistemológico. Utilizando la distinción de Kart Polanyi entre economía formal y economía sustancial, consideramos ejemplos de una economía sustancial, la cual realiza la igualdad por medio de una soberanía estratégica y un poder representativo, en términos colectivos e individuales. Estas, entre otras iniciativas, representan 'espacios de esperanza' prácticos y epistemológicos para criticar la crisis de la epistemología de mercado que infecta a los estudios de desarrollo y las relaciones internacionales.
Keywords: formal economy; international law; international relations; international trade; social control; social epistemology; sovereignty; substantive economy

The making of US monetary policy: Central bank transparency and the neoliberal dilemma - Krippner, Greta (Theory & Society, 2007)
This article explores the implications of the Federal Reserve’s shift to transparency for recent debates about neoliberalism and neoliberal policymaking. I argue that the evolution of US monetary policy represents a specific instance of what I term the “neoliberal dilemma.” In the context of generally deteriorating economic conditions, policymakers are anxious to escape responsibility for economic outcomes, and yet markets require regulation to function in capitalist economies (Polanyi ). How policymakers negotiate these contradictory imperatives involves a continual process of institutional innovation in which functions are transferred to markets, but under the close control of the state. Thus, under transparency, Federal Reserve officials discovered innovations in the policy process that enabled “markets to do the Fed’s work for it.” These innovations enlisted market mechanisms, but did not represent a retreat from the state’s active role in managing the economy.
Keywords: Board of Governors of the Federal Reserve System (U.S.); United States; capitalists & financiers; monetary policy; neoliberalism; policy sciences; public spending

Poverty, Security and the Janus-Faced State - Eadie, Pauline (The British Journal of Politics & International Relations, 2007)
In this article Polanyi's double move and Wæver's securitisation argument inform an analysis of poverty as a security issue. The inclusion of poverty on the security agenda confirms and complicates, rather than marginalises, the state as a central referent of security. It is argued that analytically and pragmatically qualitative and socially contextualised analysis of poverty offers deeper understanding than quantitative approaches. It is also argued that the rhetoric of inclusion currently espoused by the likes of the World Bank seeks to secure institutional hegemony rather than state or human security. Neo-liberal solutions to poverty premised on growth, as opposed to redistribution, mean that the states and peoples poorly equipped to compete in the capitalist game will remain impoverished. Markets and neo-liberal institutions serve to splinter, rather than coalesce, state and society.
Keywords: Copenhagen school; double movement; poverty; security

The political economy reader: markets as institutions - Barma, Naazneen; Barma, Naazneen H.; Vogel, Steven Kent (Routledge, 2007)
This reader combines in a single volume the key writings of classical and contemporary thinkers on political economy. The articles provide both a theoretical approach to understanding capitalism and a survey of the varieties of capitalism around the world today, examining the interaction between politics and markets both in theory and practice. Drawing on history, economics, political science and sociology, it emphasizes the ways in which markets are embedded in and influenced by political and social institutions. Steven K. Vogel and Nazneen Haider Barma provide an informative overview of a number of the most significant controversies and contemporary debates in political economy through the selections of contending perspectives on a variety of issues, including: How can rich countries make their economies more competitive? How can poor countries achieve economic development? How can post-communist countries make a successful transition to markets? Will theinformation technology revolution render the national varieties of capitalism obsolete? Does globalization imply that the national varieties of capitalism will converge to one global capitalism? A Political Economy Reader will be an essential resource for students of political economy and economic sociology.
Keywords: business & economics; capitalism; economics; international economic relations; political economy; political science; sociology

The Future of Sociology - Burawoy, Michael (Sociological Bulletin, 2007)
Like a hurricane, third-wave marketisation is picking up velocity and destroying societies in its path, destroying the very grounds upon which sociology grows. Sociology and humanity have a common interest in upholding civil society, and keeping state and market at bay. Working with Karl Polanyi's The Great Transformation, I diagnose three waves of marketisation associated with the commodification of labour, money and land, generating counter-movements at local, national and global levels. I argue that sociology is reshaped with each wave: in the first, it is utopian; in the second, it is driven by policy concerns; whereas emerging with the third wave marketisation is public sociology. The possibilities and challenges of public sociology as well as its relation to policy, critical and professional sociology are the subjects of this paper.
Keywords: commodification; countermovement; government policy; humanity; labor; marketisation; markets; nature; public sociology; social sciences; societies; sociology; utopian socialism

Karl Polanyi and Return of the "Primitive" in Institutional Economics - Özveren, Eyüp (Journal of Economic Issues (Association for Evolutionary Economics), 2007)
This article discusses a renewed interest in the work of scholar Karl Polanyi and the incorporation of his work into the body of institutional economics. This article discusses the notion of time in Polanyi's work and how it differs from the metaphor of time inherent in neoclassical economics. The author discusses the definition of the word "primitives" and its relationship to social policy, and how Polanyi deployed the actual state of primitives in order to replace the economistic cost-benefit analysis of the Industrial Revolution with a "social cost" alternative.
Keywords: POLANYI, Karl, 1886-1964; corporate culture; cost effectiveness; externalities; externalities (economics); industrial psychology; industrial revolution; institutional economics; social policy; social psychology

Policymaking and Learning Actors, or Is A 'Double Movement' In Cognition Possible? - Ramazzotti, Paolo (Journal of Economic Issues (Association for Evolutionary Economics), 2007)
This article discusses the relationship among economic constraints, social reform and societal pressures for a humane society, drawing on the insights of scholars Karl Polanyi and Herbert A. Simon. One of the key issues in Polanyi's work is the divergence between economic and societal values in modern capitalism. The divergence leads to a reaction against the rationale of the market and to what Polanyi refers to as the double movement. The distinction between internal consistency and external consistency is described to frame the role of institutions in the economy.
Keywords: POLANYI, Karl, 1886-1964; SIMON, Herbert A., 1916-2001; capitalism; double movement; economic policy; economic sectors; evolutionary economics; markets - social aspects; socioeconomic factors; socioeconomics

The battle of the ancient economy - Hindess, Barry (Economy & Society, 2007)
Ancient Athens and Modern Ideology addresses the battle between primitivism and modernism over the ancient economy, focusing especially on the contributions of three major figures, Max Weber, Karl Polanyi and Moses Finley. Finally, a short Epilogue returns to the examination of Marx's puzzle and his manifestly unsuccessful attempt to resolve it. Mohammad Nafissi uses this discussion to put this dispute out of its misery by advancing his own resolution of the primitivist-modernist dispute. Unfortunately, the limitations he seeks to avoid are mostly those which the supporters of one or the other side have identified in the claims of their opponents. As a result, his attempted resolution fails to disrupt their shared assumptions regarding the special place of the ancient Greeks in human development.
Keywords: Athens (Greece); FINLEY, M. I. (Moses Israel), 1912-1986; Greeks; WEBER, Max, 1864-1920; book review; history of economics; ideology; primitivism; socioeconomics

Karl Polanyi and the Modernity-versus-Postmodernity Debate - Özveren, Eyüp (European Legacy, 2007)
The originality of Karl Polanyi's (1886-1964) work in the interwar period and his work in the 1950's has gained increasing recognition in recent years, during which time the major debate on modernity has erupted. In order to link Polanyi's work with this debate, the article first discusses his legacy on the controversial concept of progress and then relates his position to this debate. Polanyi's position combines the better aspects of the two rival approaches to modernity. The article then relinks Polanyi's thought to the intellectual figures, movements, and climate of his time and thereby discloses a curious affinity between his thought and the critical theory of the Frankfurt School. This affinity can best be understood within the parameters of the historical context that they once shared.
Keywords: POLANYI, Karl, 1886-1964; debates and debating; economics; modern society; modernity; postmodernism (philosophy); progress

The Early Debate on Economic Calculation in Vienna (1919-1925): The Heterodox Point of View: Neurath, Mises and Polanyi - Becchio, Giandomenica (Storia del Pensiero Economico: Nuova Serie, 2007)
This paper is based on the idea that the early debate on economic calculation in a planned economy conducted in Vienna among Neurath, Mises, and Polanyi (1919-1925) was the starting point for the development of a particular form of heterodox economic theory propounded by liberal thinkers like Mises and by socialists like Neurath and Polanyi. Mises claimed that solving the problem of calculation was impossible, and consequently that a centrally planned economy was not theoretically feasible. Neurath and Polanyi instead sought to solve the problem of calculation and, despite certain profound differences between their views, they proposed a socialistic model alternative to the orthodox Marxist one.
Keywords: MISES, Ludwig von; Marxism; NEURATH, Otto; economic calculation; economic thought; heterodox economic theory; heterodox economics; history of economic thought; history of economics; planned economy

Against the Law: Labor Protests in China’s Rustbelt and Sunbelt - Lee, Ching Kwan (University of California Press, 2007)
This study opens a critical perspective on the slow death of socialism and the rebirth of capitalism in the world's most dynamic and populous country. Based on remarkable fieldwork and extensive interviews in Chinese textile, apparel, machinery, and household appliance factories, Against the Law finds a rising tide of labor unrest mostly hidden from the world's attention. Providing a broad political and economic analysis of this labor struggle together with fine-grained ethnographic detail, the book portrays the Chinese working class as workers' stories unfold in bankrupt state factories and global sweatshops, in crowded dormitories and remote villages, at street protests as well as in quiet disenchantment with the corrupt officialdom and the fledgling legal system.
Keywords: China; cultural anthropology; double movement; fictitious commodities; labour; social anthropology

Non-Trade Concerns in Agricultural and Environmental Economics: How J.R. Commons and Karl Polanyi Can Help Us - Barthélemy, Denis; Nieddu, Martino (Journal of Economic Issues, 2007)
Keywords: COMMONS, J.R.; economics; environmental economics; substantive economy

The Polanyian Way? Voluntary Food Labels as Neoliberal Governance - Guthman, Julie (Antipode, 2007)
Voluntary food labels that express ecological, social, and/or place-based values have been posed as an important form of resistance to neoliberalization in the Polanyian sense of protecting land, other natural resources, and labor from the ravages of the market. At the same time, these labels are in some respects analogs to the very things they are purported to resist, namely property rights that allow these ascribed commodities to be traded in a global market. After reviewing the Polanyian claims about these labels, the paper examines how these labels are operationalized and notes important differences in the sort of barriers to entry they erect, which in turn have quite different distributional consequences. It then goes on to discuss how these labels look to be an expression of roll-out neoliberalization. Following Heynen and Robbins who note four dominant aspects of neoliberalization of environmental governance (governance, privatization, enclosure, and valuation), to which a fifth (devolution) is added, the paper shows how these labels not only concede the market as the locus of regulation, but in keeping with neoliberalism's fetish of market mechanisms, they employ tools designed to create markets where none previously existed. In recognition that neoliberal political economies and subjectivities have delimited the possible, the paper also grapples with how these labels may produce political openings outside of their most proximate effects.
Keywords: agro-food governance; community studies; depletion allowances; fair trade; food labeling; government ownership; labeling; liberalism; natural resources; neoliberalism; organic food; privatization

Philosophizing with a hammer? A critique of Mirowski's markomata informed by continental philosophy - Juniper, James (Journal of Economic Behavior & Organization, 2007)
Abstract: Mirowski''s justification for replacing the foundational principles of neoclassical economics – methodological individualism and rational choice theory – with a theoretical framework informed by cybernetics, information theory, and computational biology, is subject to a critique informed by the work of Karl Polanyi, Michel Foucault and Jürgen Habermas. Mirowski''s proposed alterative is called into question on the basis of two crucial weaknesses. First there is Mirowksi''s penchant for what Polanyi has called Laplacian reductionism. Second there is Mirowski''s inability to develop a comprehensive and consistent theory of evolutionary economics. Mirowski''s work is questioned in terms of what social theorists call the ‘structuration paradox’.
Keywords: FOUCAULT, Michel, 1926-1984; MIROWSKI, Philip; continental philosophy; cybernetics; economic methodology; economics; social theory; structuration paradox

Conflict of Laws as Constitutional Form: Reflections on International Trade Law and the Biotech Panel Report - Joerges, Christian (Social Science Research Network, 2007)
Hardly anywhere is the trend towards a perfection of transnational governance arrangements and their “legalization” more visible than in international trade. Governance arrangements established through and alongside WTO law are both practically important and theoretically challenging. They do not just organise international trade relations. They also affect national and regional (European) regulatory policies partly directly, partly more indirectly. How can we explain and how should we evaluate their emergence? The WTO system of 1994, which replaced the GATT of 1947, responded to the ever increasing importance of non-tariff barriers to trade. These barriers reflect regulatory concerns especially in the fields of health and safety, consumer and environmental protection. There importance for WTO member is such that they cannot simply be abandoned for the sake of free trade. This is why the responses the new international trade system institutionalised by special agreements concerning on-tariff barriers to free trade such as the Agreement on the Application of Sanitary and Phytosanitary Measures (SPS) and the Agreement on Technical Barriers to Trade (TBT) reflect a politicisation of international trade. Can we conclude that international markets have been re-regulated and that international trade law ensures their “social embeddedness”? The paper seeks yardsticks for an answer to these questions in the debates on transnational constitutionalism. It submits that constutionalisation can and should be based on a conflict-of approach. For its elaboration of this suggestion, the paper first contrasts the jurdification of transnational governance at the European and the international level. It then discusses the WTO panel report on the Biotech dispute. It concludes that the legalisation and judicialisation in that case have remained “thin.” What can be observed is a political rather than a social and legal embeddedness of markets.
Keywords: FOUCAULT, Michel, 1926-1984; Polanyi and Foucault; World Trade Organization (WTO); constitutionalisation; economic law; embeddedness; european governance; international trade; legal embeddedness; legalization; legitimacy; multilevel governance; national autonomy; risk regulation; social embeddedness; transnational governance

Globalization, inequalities and the “Polanyi problem” - Śliwa, Martyna (Critical perspectives on international business, 2007)
The purpose of this paper is to contribute to the debate on the consequences of globalization, in particular the increasing disparity between the wealth of nations and individuals in society. It discusses mechanisms which lead to perpetuation and reinforcement of the situation in which, despite being characterized by inequalities and fragmentation, societies remain by and large cohesive and stable. This article engages with the so-called “Polanyi problem” and with Polanyi’s and other authors’ responses to it. In the discussion, the analytical approach is adopted by reference to Aldous Huxley’s Brave New World, in particular his concept of soma. Using the metaphor of soma, developed into four interrelated dimensions, illustrations of social and organizational processes, which ensure sustainability of, and cohesion within, a society based on inequality and fragmentation, are indicated. It is argued that the existence of stratified societies, and inequalities of wealth within and between them, is accompanied by phenomena which support and sustain them. Drawing upon literary fiction can offer valuable insights into issues pertinent to contemporary academic debate. Engagement with Huxley’s work provides an alternative way of contributing to the globalization debate and, in particular, to the literature addressing the so-called “Polanyi problem”.
Keywords: Brave New World (book); HUXLEY, Aldous; Polanyi problem; distribution of wealth; globalization; international business; society; soma

Neoliberalism, embedded neoliberalism and neocorporatism: Towards transnational capitalism in Central-Eastern Europe - Bohle, Dorothee; Greskovits, Béla (West European Politics, 2007)
This article analyses the key features and origins of three variants of transnational capitalism emerging in Central-Eastern Europe: a neoliberal type in the Baltic states, an embedded neoliberal type in the Visegrád states, and a neocorporatist type in Slovenia. These regimes are characterised by their institutions and performances in marketisation, industrial transformation, social inclusion, and macroeconomic stability. Explanations for regime diversity are developed at two levels. First, it is argued that the legacies of the past, and their perceptions as either threats or assets to these countries' future, have had deep impact on regime types. Legacies and initial choices were no less crucial for the degree of democratic inclusion, and the different patterns of protest and patience on the paths towards the new regimes. Second, the article demonstrates the importance of transnational influences in industrial transformation and social inclusion.
Keywords: Central-Eastern Europe; embedded neoliberalism; neoliberalism; transnational capitalism

Public sociology vs. the market - Burawoy, Michael (Socio-Economic Review, 2007)
Building on Karl Polanyi's theory of a societal reaction to the unregulated exchange of what he called fictitious commodities—labour, money and land—this paper links the history of sociology to the history of the market. If the first wave of marketization in the nineteenth century dwelt on the commodification of labour, prompting utopian sociologies, and the second wave of marketization of the twentieth century was provoked by the commodification of money, generating national policy sociologies, then the third wave of marketization that began in the last quarter of the twentieth century includes the commodification of the environment (land, air, water), and calls for public sociologies of a global dimension.
Keywords: commercial products; fictitious commodities; government policy; history of sociology; markets - social aspects; publicity - social aspects; social theory; socioeconomics; utopian socialism

The Transnational Politics of Corporate Governance Regulation - Overbeek, Henk; Apeldoorn, Bastiaan van; Nölke, Andreas (Routledge, 2007)
This ambitious volume explores the politics of recent changes in corporate governance regulation and the transnational forces driving the process. Corporate governance has in the 1990s become a catchphrase of the global business community. The Enron collapse and other recent corporate scandals, as well as growing worries in Europe about the rise of Anglo-Saxon finance, have made issues of corporate governance the subject of political controversies and of public debate. The contributors argue that the regulation of corporate governance is an inherently political affair. Given the context of the deepening globalization of the corporate world, it is also increasingly a transnational phenomenon. In terms of the content of regulation the book shows an increasing reliance on the application of market mechanisms and a tendency for corporations themselves to become commodities. The emerging new mode of regulation is characterized by increasing informalization and by forms of private regulation. These changes in content and mode are driven by transnational actors, first of all the owners of internationally mobile financial capital and their functionaries such as coordination service firms, as well as by key public international agencies such as the European Commission. The Transnational Politics of Corporate Governance Regulation will be of interest to students and researchers of international political economy, politics, economics and corporate governance.
Keywords: NGOs; NGOs (non-governmental organizations); business & economics; economic policy; international political economy; political science; public policy

Understanding the Diverging Trajectories of the United States and Western Europe: A Neo-Polanyian Analysis - Block, Fred (Politics & Society, 2007)
This article proposes a neo-Polanyian theoretical framework for understanding the dynamics within contemporary market societies. It uses this framework to analyze the divergence between the United States and other developed societies that has become more pronounced in the first years of the twenty-first century. The argument emphasizes the shifting political alliances of the business community in the United States and suggests that from 1994 onward, business lost power in the right-wing coalition to its religious Right allies. The growing power of a religious-based social movement is a critical ingredient in the unilateralist turn in the Bush Administration’s foreign policy.
Keywords: U.S. business; economic sociology; embedded economy; embeddedness; social theory; varieties of capitalism

Principles of Institutional-Evolutionary Political Economy -- Converging Themes from the Schools of Heterodoxy - O'Hara, Phillip Anthony (Journal of Economic Issues (Association for Evolutionary Economics), 2007)
The article examines the renewed interest in heterodox political economy. Institutionalists, post Keynesians, neo-Marxists, and feminists among others, and various sub-groups provide schools of thought on heterodoxy. The guidelines of institutional-evolutionary political economy (IEPE) are offered alongside socioeconomic analysis and complexity theories. The author outlines the conflict of individual v. structure. Other topics covered include social capital, heterogeneous agents, financial instability, cumulative causation, institutional environments, community and governance, and destructive creation.
Keywords: Keynesian economics; creative destruction; disembedded economy; economic policy; evolutionary economics; heterodox economics; heterodox political economy; infrastructure (economics); mixed ability grouping (education); political economic analysis; social capital; social theory

Tanzanite: Commodity Fiction or Commodity Nightmare? - Donahue, Katherine Curtis (Social Science Research Network, 2007)
Karl Polanyi's discussion of the commodification of land, labour, and money is useful in analysis not only of nineteenth century markets but also of twenty-first century social and economic developments. This working paper explores the process of commodification of tanzanite, a gemstone discovered in the 1960s south of Mt. Kilimanjaro, Tanzania, and actively mined only since the 1980s. More rare than diamonds because the source area is limited to the Mererani hills east of Arusha, the gemstones reach markets through Maasai middlemen, foreign buyers, processors, cutters, polishers and dealers in Tanzania, India, Hong Kong, and the United States. The U.S. is responsible for 80% of the market for tanzanite. Production of the stone is occasionally slowed by flooding, accidents, and conflict over rights to mining areas. Children and teenagers often work in the tanzanite mines. These miners suffer death and disease not only because of unsafe mine conditions but also because of drug use and HIV/AIDS. Furthermore, this new commodity received close scrutiny after the attacks of September 11, 2001, because of a Wall Street Journal report that members of al Qaeda bought tanzanite for use in funding its networks and activities. This paper explores policy issues raised not only by that report and by global NGOs such as Global Witness, but also by the Tanzanian state, by health and safety workers and the miners and mining companies at Mererani. The paper is based on field interviews with buyers and sellers, in Tanzania and in the United States, as well as analysis of media reports, in order to argue that this particular commodity is, in Polanyi's terms, a fiction, one which has serious policy, social, health, and economic implications.
Keywords: Tanzania; Tanzanite; fictitious commodities; mining

The Great Transformation of Embeddedness: Karl Polanyi and the New Economic Sociology - Beckert, Jens (Social Science Research Network, 2007)
I argue that in its adaptation from Karl Polanyi’s The Great Transformation, the concept of embeddedness has itself undergone a great transformation. In the process, significant meanings of the concept have vanished, while others have been added. First I explore the different meanings the concept of embeddedness has achieved in the new economic sociology. Then I argue that it is not the embeddedness of economic action that should constitute the vantage point of economic sociology, but rather three coordination problems that actors face in economic exchange: the valuation of goods, competition and the problem of cooperation deriving from the social risks of exchange. I show that by proceeding from these coordination problems economic sociology, economic anthropology and economic history can find common research questions which allow them to enter into dialogue with each other more systematically. In the next section I focus on the social-reformist inclinations of Polanyi’s use of the notion of embeddedness and thereby highlight a challenge posed in The Great Transformation that was largely not taken up by economic sociologists. Finally, I discuss limitations for developing a macro theory of the economy that result from making embeddedness the core concept of economic sociology.
Keywords: economic history; economic sociology; embeddedness; political economy

Embeddedness, Path Dependency and Social Institutions: An Economic Sociology Approach - Ghezzi, Simone; Mingione, Enzo (Current Sociology, 2007)
This paper argues for a theoretical approach based on embeddedness which assumes that the economic actor is not an atomized and utilitarian individual, but is in fact positioned within specific historical and institutional contexts in various social networks. This approach is based on Polanyi's critically debated contribution which allows for an empirical study of the diversity of institutional structures and of the significance of configurations of insertion within different social networks. Such diversity results from the double movement of disembeddedness and re-embeddedness caused by the spread of constantly emerging market opportunities, and by the importance held by the historically and culturally different selective processes of path dependency in the construction of the institutions of social regulation and of the socialized preferences of economic actors. Within these processes attention is given to the transformation of social systems based on reciprocity (household, kin, social capital networks, etc.), associations of shared interests, forms of economic organization (in a plurality of coexisting ‘economies’), unequal distribution of power, and political intervention.
Keywords: abordaje de sociologí económica; culture; dependencia de camino e institutiones sociales; developing countries; dépendance au chemin parcouru; embeddedness; empirical research; entrepreneurship; imbricación; institutions sociales; kin network; market; path dependency; reciprocity; reciprocity (commerce); social groups; social institutions; social networks; social systems; socioeconomics; utilitarianism

The End of Potlatch: An Anthropological Approach to Nostromo - Juhász, Tamás (Research in Economic Anthropology, 2007)
This study contends that the various forms of archaic trade that anthropologists have reconstructed on the Northwest Coast of America are explanatory of plot-construction and characterization in Conrad's South-American novel. My thesis is that Nostromo is a figure defined by the practice of potlatch, and that his key presence in the plot entails the representation of a culturally dislocating transition from archaic transactions to modern commerce. The theoretical framework of this chapter hinges on the insights of Marcel Mauss, Claude Lévi-Strauss, Karl Polanyi, and Georges Bataille.
Keywords: CONRAD, Joseph; LEVI-STRAUSS, Claude; Nostromo (book : Conrad); archaic economy; embeddedness; history of commerce; plots (Drama, novel, etc.); potlatch; reciprocity; redistribution

Globalization, Inequality, and "Double Movement" in East Asia - Kim, Wonik (Conference Papers -- New England Political Science Association, 2007)
The purpose of this paper is to analyze the effects of rising income inequality on the welfare state in East Asia. Specifically, I explore and test two causal links: 1) the effects of economic globalization on income distribution, and 2) the increase in income inequality on the prospect of socio-welfare policies. Building on Polanyi's politico-economic concept of "double movement," I hypothesize that rapid neoliberalization and financial globalization in East Asia since the early 1990s (after the Asian Financial Crisis) has de-constructed the traditional state apparatuses that supported a well-known state-led accumulation strategy. This shift in political arrangements and national growth strategy, in turn, has entailed rising income inequality in a society, calling for restructuring the traditional East Asian welfare state. The success and failure of the creation of a new welfare state for new social risks depends on the level of contentious politics and country specific traits. With this general theoretical framework, I conduct a comparative method of five East Asian countries - China, Japan, South Korea, and Taiwan - for the period from the 1990s to the present, and explain the similarities and differences among them. ..PAT.-Unpublished Manuscript
Keywords: East Asia; equality; globalization; income distribution; international competition; neoliberalism

Rethinking the Categories of Feminist Theory: Diverse Feminist Responses to the Market Economy - MacLean, Lee (Conference Papers -- New England Political Science Association, 2007)
Feminist theory is often articulated as a series of categories of thought: liberal feminism, socialist feminism, Marxist feminism, psychoanalytic feminism, etc. These categories have aided the recent development of feminist thought, but their prevalence sometimes limits discussion to predicable perimeters. My argument begins from the observation that feminists often have very different responses to the rise of the market economy as a separate institution largely free of control by political and kinship-based authorities. In particular, there is a difference of opinion about the liberating possibilities of participating in a largely self-regulating market economy. I think an investigation of this disagreement could provide a new way of conceptualizing the main lines of feminist argument. For example, feminists who emphasize that the market economy provides an opportunity for women to free themselves from gender restrictions expressed in family and kinship traditions might be called libertarian-type feminists. Other feminists, those who (from varying perspectives) are skeptical that participation in the free market results in freedom for women, might be termed free-market skeptics. Of course, one wants to avoid creating new rigid labels, but thinking about this conceptualization can help to destabilize old categories and to recast often divisive debates (for example, over issues such as prostitution, pornography and housework).The argument is inspired by thinking through descriptions of the historically changing relations between market, family and politics found in two works: Karl Polanyi's The Great Transformation and Linda Nicholson's "Feminism and Marx: integrating Kinship with the Economic." ..PAT.-Unpublished Manuscript
Keywords: capitalism; families; feminism; feminists; kinship; women

Reforming Social Justice in Neoliberal Times - Brodie, Janine M (Studies in Social Justice, Vol 1, Iss 2, Pp 93-107 (2007), 2007)
This article unfolds in three stages. First, it locates the emergence of modern conceptions of social justice in industrializing Europe, and especially in the discovery of the “social,” which provided a particular idiom for the liberal democratic politics for most of the twentieth century. Second, the article links this particular conception of the social to the political rationalities of the postwar welfare state and the identity of the social citizen. Finally, the article discusses the myriad ways in which this legacy of the social and social justice has been disrupted, although not yet fully displaced, by the economic orthodoxies and individualization that inform the contemporary neoliberal governing project in Canada. The result, the article concludes, has been the institutionalization of insecurity, which demands the renewal of a social way of seeing and a politics of social justice on local and global scales.
Keywords: criminology; neoliberalism; political economy; social and public welfare; social governance; social justice; social pathology; social policy; social sciences; sociology

Reading Karl Polanyi for the Twenty-First Century - Bugra, A. (Palgrave Macmillan, 2007)
Using Karl Polanyi's analysis of the separation of politics and the economy, the book argues that the market economy is not a spontaneous process, but a...
Keywords: commodification; financial economics; macroeconomics; market economy; monetary economics

Reconfiguring the Terrain of Cultural Governance in Mexico: The Role of the Mexican Film Community in the Era of Neoliberal Globalization - Busmann, Nadine (2007)
Reconfiguring the Terrain of Cultural Governance in Mexico: The Role of the Mexican Film Community in the Era of Neoliberal Globalization Embracing the dominant neoliberal project, many Mexican elites have prioritized economic growth and market logics over broader social goals. The unleashing of market forces globally,and the adoption of neoliberal policies nationally have had a significant impact on local communities and national culture in Mexico. Focusing on Mexican cultural production, this paper explores the shifting terrain of political struggle in the Mexican film industry. One of the central concerns of this paper is what processes and on what authority the imagined political community in Mexico is constructed, reconstructed, and reproduced in the current era of neoliberal globalization. Historically, political contestation among political, cultural and business elites has been central to the perpetuation of the national cultural project, in this paper, it is argued that the changing political landscape in Mexico has created new conditions for contestation providing sites for previously marginalized forces to challenge the hegemony of neoliberalism.Conceptualising neoliberal globalization and its application by Mexican elites in Polanyian terms?as a double movement?the paper examines the consolidation of the Mexican film coalition as a counter-movement, driven by cultural elites, which emerged to contest the hegemony of market driven politics. In this regard the paper analyzes the ideological and material foundations of this movement. Further, it examines the coalition´s efforts to create a social base from which to reshape the state´s politico-cultural agenda to ensure the survival of an indigenous film industry, thus providing (sub)national identities with an image and voice in the face of globalizing forces. It suggests that organic intellectuals built collective political agency upon the conviction that neoliberal globalization is to be resisted insofar as it subjects the nation to transnational?and hence alien?cultural, political and economic forces. Lastly, it challenges the assumption that in challenging the hegemony of neoliberalism the film community is anti-capitalist. As the evidence will reveal the motivating factors and ideological foundations driving the efforts of the film community are much more complex. ..PAT.-Unpublished Manuscript
Keywords: Mexico; cultural production; elite (social sciences); globalization; international studies; neoliberalism; social goals

Third Ways: How Bulgarian Greens, Swedish Housewives, and Beer-swilling Englishmen Created Family-centered Economies-- and why They Disappeared - Carlson, Allan C. (ISI Books, 2007)
Freewheeling capitalism or collectivist communism: when it came to political-economic systems, did the twentieth century present any other choice? Does our century? In Third Ways, social historian Allan Carlson tells the story of how different thinkers from Bulgaria to Great Britain created economic systems during the twentieth century that were by intent neither capitalist nor communist. Unlike fascists, these seekers were committed to democracy and pluralism. Unlike liberal capitalists, they refused to treat human labor and relationships as commodities like any other. And unlike communists, they strongly defended private property and the dignity of persons and families. Instead, the builders of these alternative economic systems wanted to protect and renew the “natural” communities of family, village, neighborhood, and parish. They treasured rural culture and family farming and defended traditional sex roles and vital home economies. Carlson's book takes a fresh look at distributism, the controversial economic project of Hilaire Belloc and G. K. Chesterton which focused on broad property ownership and small-scale production; recovers the forgotten thought of Alexander Chayanov, a Russian economist who put forth a theory of “the natural family economy”; discusses the remarkable “third way” policies of peasant-led governments in post–World War I Bulgaria, Poland, and Romania; recounts the dramatic and largely unknown effort by Swedish housewives to defend their homes against radical feminism; relates the iconoclastic ideas of economic historian Karl Polanyi, including his concepts of “the economy without markets” and “the great transformation”; and praises the efforts by European Christian Democrats to build a moral economy on the concept of homo religious—“religious man.” Finally, Carlson's work explains why these efforts—at times rich in hope and prospects—ultimately failed, often with tragic results. The tale inspires wistful regret over lost opportunities that, if seized, might have spared tens of millions of lives and forestalled or avoided the blights of fascism, Stalinism, socialism, and the advent of the servile state. And yet the book closes with hope, enunciating a set of principles that could be used today for invigorating a “family way” economy compatible with an authentic, healthy, and humane culture of enterprise.
Keywords: business & economics; economic history; economic theory; economics / comparative; history - modern; history / 20th Century

The Politics of Liquid Modernity: Polanyi and Bauman on Commodification and Fluidity - Christodoulidis, Emilios (Liquid Society and Its Law, 2007)
Book edited by Jirí Pribán This collection of essays brings together Zygmunt Bauman and a number of internationally distinguished legal scholars who examine the influence of Bauman's recent works on social theory of law and socio-legal studies. Contributors focus on the concept of 'liquid society' and its adoption by legal scholars. The volume opens with Bauman's analysis of fears and policing in 'liquid society' and continues by examining the social and legal theoretical context and implications of Bauman's theory.
Keywords: BAUMAN, Zygmunt; commodification; fluidity; law / jurisprudence; liquid modernity; philosophy; political philosophy

Neoliberalism or Democracy: Competing Forms of Social Organization in Latin America - Dowd, Jeffrey (Conference Papers -- American Sociological Association, 2007)
While political turmoil is not new to Latin America, the tension between neoliberalism and democracy can help explain present-day turmoil. The current political situation in Latin America is the result of a disconnect between the goals of democracy, in particular, between social justice goals, upon which the legitimacy of democratic government rests, and the neoliberal economic policy of the region. Polanyi's concept of the always-embedded economy states that a market economy must be embedded in a market society. Following Polanyi, I argue that markets and democracy require different forms of social organization. Markets and democracy are alternate and competing forms of social organization. The predominance of one often coincides with the restriction of the other. For example, neoliberal governance that maintains market society undermines electoral efficacy. While this may be a general attribute of neoliberalism, previous economic crisis in Latin America increased the need for rhetorical commitment to social justice goals. Latin America's structural position has not changed, however, and international finance and global organizations, like the International Monetary Fund and the World Bank, still constrain Latin American governments. I argue that any resolution to the tension between neoliberalism and democracy must accept the conflicting nature of these two forms of social organization. ..PAT.-Unpublished Manuscript
Keywords: Latin America; always embedded economy; democracy; economic policy; embeddedness; free market; free-market; market; neoliberalism; political science; political theory; social justice

Moral Views of Market Society - Fourcade, Marion (Annual Review of Sociology, 2007)
Upon what kind of moral order does capitalism rest? Conversely, does the market give rise to a distinctive set of beliefs, habits, and social bonds? These questions are certainly as old as social science itself. In this review, we evaluate how today's scholarship approaches the relationship between markets and the moral order. We begin with Hirschman's characterization of the three rival views of the market as civilizing, destructive, or feeble in its effects on society. We review recent work at the intersection of sociology, economics, and political economy and show that these views persist both as theories of market society and moral arguments about it. We then argue that a fourth view, which we call moralized markets, has become increasingly prominent in economic sociology. This line of research sees markets as cultural phenomena and moral projects in their own right, and seeks to study the mechanisms and techniques by which such projects are realized in practice.
Keywords: capitalism; culture; governmentality; moral markets; moral order; performativity

Globalization, Welfare Reform and the Social Economy: Developing and Alternative Approach to Analyzing Social Welfare Systems in the Post-Industrial Era Special Issue on Globalization: Social Justice & Social Welfare - Gonzales, Vanna (Journal of Sociology and Social Welfare, 2007)
Our understanding of the relationship between globalization and contemporary social welfare systems is heavily influenced by three conventional approaches to studying welfare reform: the political economy, moral economy, and mixed economy approaches.In addition to analyzing the strengths and weaknesses of each of these approaches, a central aim of this article is to introduce the social economy approach as an emergent alternative. Drawing from a growing body of work on institutional innovation within the European third sector, I argue that the social economy approach makes a valuable contribution to understanding the role of welfare networks in recon-figuring globalizations 'impact on the character and quality of social provision so as to better reconcile social efficacy with social justice.
Keywords: globalization; social enterprises; social inclusion; social justice; third sector; welfare networks; welfare reform

Searching for the Theory of Practice behind the WTO's Commodification Mandate - Göpel, Maja (2007)
When trying to understand the origins of the collapse of nineteenth-century civilization, Karl Polanyi identified a Great Transformation into a "starkly utopian" Self-Regulating Market (SRM). This shift entailed 2 elements: a wide-ranging re-regulation of organization and control of production processes, and the development of economic liberalism as a body of thought that provided justification of a new set of public policies that facilitated a transformation of land (nature), labor (people), and capital (money) into "fictitious commodities." Even though these factors have not originally been produced for sale, they are now organized by purchase-logics and their value determined by market signals. Philosophy of praxis approaches point out that this process of transformation is never complete. Neither the ?discovery? of new commodities, nor the expansion of market logics are natural, but the outcome of socio-political struggles. New agreements of the World Trade Organization for example render ever more elements of social life and nature as ?trade related? and under its auspices the next great commodification wave unfolds. This paper traces which type of knowledge publicly justifies the resulting floods these policies release before comparing it with concrete negotiated outcomes and their impacts. The final discussion will circle the question to which extent ?objective? science influences policy-making - or if subjective selection of sciences supports policy-selling. ..PAT.-Unpublished Manuscript
Keywords: World Trade Organization (WTO); commodification; ideal types; institutionalism; international trade; manufacturing processes; methodology; policy sciences; trade regulation

The Political Economy of Mesoamerican States: An Economic Ethnographer's View - Halperin, Rhoda (The Political Economy of Ancient Mesoamerica: Transformations During the Formative and Classic Periods, 2007)
KM: outlines a generic model of political economy based on Polanyi's writings and explores some of its implications.
Keywords: Mesoamerica; economic anthropology

The Intellectual Commons vs Intellectual Property: Marxian and Polanyian Perspectives on Intellectual Capital, including Remarks on Primitive Accumulation - Jessop, Bob (2007)
This paper explores the increasing significance of intellectual property rights for the appropriation of surplus value in capitalism. Building on Marx's analysis of the value form and extending it to the commodification of knowledge, it develops a Marxian critique of informational capitalism based on the basic categories of value theory; inter alia, this looks at the commodification of knowledge from the viewpoint of commodity fetishism, the enclosure of traditional knowledge, the formal subsumption of intellectual labour, the real subsumption of intellectual labour, and the role of intellectual property rights as a contradictory means to support the average rate of profit for firms specializing in immaterial production (whilst enabling them to appropriate monopoly profits). The second part of the paper inquires whether these arguments lend support to a Polanyian interpretation of knowledge as a fictitious commodity. On the basis of the arguments already deployed, plus further arguments, it is suggested that knowledge can function as a non-commodity, a quasi-commodity, a fictitious commodity, a real commodity, and as fictive capital. This has interesting implications for the concepts of primitive accumulation and accumulation through dispossession. ..PAT.-Unpublished Manuscript
Keywords: Marxist philosophy; capitalism; commodification; intellectual property; political doctrines

Karl Polanyi, Marshall Sahlins, and the Study of Ancient Social Relations - Kirk, Alan (Journal of Biblical Literature, 2007)
Questions arise whenever social-scientific models are used in analysis of ancient texts, particularly regarding the feasibility of their application to social and cultural milieux different from those from which they were derived. An essay I authored that assessed the command in Luke 6 to "love your enemies" from the perspective of ancient reciprocity ethics, and that invoked Marshall Sahlins's taxonomy of reciprocity relations (general, balanced, and negative reciprocity), was queried by Zeba Crook on precisely this point, namely, whether it applied Sahlins's taxonomy to Greco-Roman reciprocity relations without adequate attention to the distinctions between kinship organized tribal societies (the focus of Sahlins's analysis) and the socially stratified agrarian societies characteristic of the ancient Mediterranean world.1 Crook's piece was more than just a critique on that point; it raised questions about the extent to which Sahlins's model has applicability to the Roman world. This essay will focus on this key point and, it is hoped, will also contribute to the discussion on the use of social-scientific research in biblical studies.
Keywords: SAHLINS, Marshall; biblical studies; clientelism; cognitive models; economic models; kinship; reciprocity; slave trade; social interaction; stone age

Embeddedness and the intellectual projects of economic sociology (English) - Krippner, Greta R. [b1] (analytic); Alvarez, Anthony S. [b2] (analytic) (Annu. rev. sociology, 2007)
In this review, we explore how the concept of embeddedness has shaped-and been shaped by-the evolution of the subfield of economic sociology. Although embeddedness is often taken as a conceptual umbrella for a single, if eclectic, approach to the sociological study of the economy, we argue that in fact the concept references two distinct intellectual projects. One project, following from Granovetter's (1985) well-known programmatic statement, attempts to discern the relational bases of social action in economic contexts. Another project, drawing from Polanyi's [1944 (2001), 1957 1977] social theory, concerns the integration of the economy into broader social systems. Critically, these two formulations of embeddedness involve different views of the relationship between the economic and the social. The implication is that the obstacles to theoretical integration in economic sociology, while not insurmountable, are greater than is typically acknowledged. (English)
Keywords: GRANOVETTER, Mark; Réseau; action sociale; economic sociology; economic system; economy & society; economy/society; embeddedness; firms; marché; market; markets; network; networks; social action; système économique

The Slight Transformation: Contesting the Legacy of Karl Polanyi - Lacher, Hannes (Reading Karl Polanyi for the Twenty-First Century, 2007)
The postwar reconstruction of domestic and international orders ushered in a new political economy of capitalism. It entailed a far-reaching reorganization of social relations and economic institutions and accorded to the state an important role in the management of the economy. Many of the institutions of classical liberalism were displaced by interventionist mechanisms. The welfare state consolidated and extended multifarious forms of protection accorded to labor. A new level of labor-market regulation and public provisioning transformed the conditions under which people worked and lived, leading to higher incomes for large groups of society, and creating a higher degree of security for them both in the workplace and beyond. International institutions were created to facilitate the regulatory functions that these welfare states had assumed, supported by a conducive exchange-rate regime and restrictions on capital mobility.
Keywords: capital mobility; market society; market system; postwar period; postwar reconstruction; welfare state

India's Double-Movement: Polanyi and the National Alliance of People's Movements - Levien, Michael (Berkeley Journal of Sociology, 2007)
Through an examination of India's National Alliance of People's Movements (NAPM), the largest social movement alliance resisting neoliberal globalization in India, this paper attempts to theoretically reconstruct Polanyi's theory of (t the double movement" for the neoliberal age. Polanyi famously observed that early twentieth century liberal attempts to "dis-embed" the market from social controls created unprecedented social dislocations, leading to widespread protective (< countermovements "to "re-embed" the market within social constraints. I analyze the usefulness and shortcomings of Polanyi's formulation for understanding the current politics of neoliberal globalization. Specifically, I argue that Polanyi failed to explain how a "countermovement" is politically organized and did not develop an adequate theory for the anti-market countermovement he described. Using ethnographic observation ofNAPM's efforts to organize a national alliance against neoliberal globalization, I show how the nature of a "Polanyian" constituency creates previously untheorized obstacles for the effective political organization of a countermovement. These obstacles derive from inherent characteristics of a Polanyian constituency: 1) the economic and social diversity of—and therefore potential antagonism between—its prospective agents, who do not share similar relationships to the means of production, but only the common fact of being negatively affected by the market, and 2) the vastly different ways in which such diverse groups experience market displacements, leadings to a proliferation of single-issue movements whose commonality is hard to perceive and unity difficult to build.
Keywords: India; constituents; double movement; globalization; international alliances; neoliberalism; protest movements; resistance movements; social movements

On the need for a heterodox health economics - McMaster, Robert (post-autistic economics review, 2007)
INTRO: This paper is a plea for greater cognizance of the errors of omission and commission committed by mainstream health economics, and the potential orientation in treating health and health care as (metaphorical) commodities that the unfettered influence of health economics may be prompting. Economic criticisms of mainstream health economics are evident, especially in the collection edited by John Davis (2001), but tend to be rather fragmented and lacking in credibility with our mainstream brethren. Contentiously, seeking the approval or otherwise of the mainstream is perhaps not as important as in other areas of economics, if indeed it is the case at all, but gaining the attention of other social scientists, medics, and policy makers may be of considerable consequence. The paper does not seek to speculate on strategies for addressing these bodies; instead it concentrates on the nature of the message.
Keywords: commodity fiction; fictitious commodities; health; health economics; political economy

Four Horsemen of the Apocalypse: Marx, Weber, Schumpeter, and Polanyi - Özel, Hüseyin (ICAPE Conference: “Economic Pluralism for the 21st Century”., 2007)
This paper is an attempt at developing an analytical framework that could be helpful to understand the unstable character of the capitalist society, by drawing upon the work of four important thinkers: Marx, Weber, Schumpeter, and Polanyi. It is argued that all four share a similar vision towards capitalism, and that they are all indispensable for the thesis that the working of capitalism undermines its own institutional structure, and thus make the reproduction of the capitalist society a contradictory process. The paper advances three theses in regard of these thinkers: first, being various representatives of the German “expressivist ” tradition, they conceive human history as displaying two antinomical tendencies at the same time; namely, human self expression through creative action vs. the loss of freedom due to increasing rationalization, alienation, and domination; second, capitalism should be seen as a decisive step towards more rationalization and therefore the loss of freedom, even if it creates the preconditions of the self-realization of the “species-being”; and third, they all believe that the very success of capitalism is the basic cause of its failure.
Keywords: MARX, Karl, 1818-1883; SCHUMPETER, Joseph Alois, 1883-1950; WEBER, Max, 1864-1920; alienation; creative destruction; double movement; iron cage

Linking Political Economic Projects and Pension Systems in Europe: A Comparison of the Role of Occupational Pension Funds as Investment Actors in Three European Countries - Roumpakis, Antonios (Conference Papers -- International Studies Association, 2007)
The paper explores the relation of different political economic projects and the development of pensions as a social right in three countries: Sweden, Germany and United Kingdom. It comprises three parts. The first part provides the conceptual framework, which combines a Polanyian perspective for the social embeddedness of markets with a three dimensional power theoretical approach in order to analyse modes of governance as practices of socio-economic regulation. The second part identifies the link between the macro-level of analysis i.e. different political economy logics and modes of governance and the meso-level of analysis i.e. the institutional paths that these countries have followed in developing their pensions systems and what used to be and currently is the role of occupational pension funds in them. This type of funds offers a prime example of how institutions that originally developed within a logic of social rights have now become actors in the economy. The decision-making of this new actor is however depended on the power relations between labour and capital in each country. The third part of the paper continues to show how the institutional paths have departed from their national spatio-temporal fix and have been re-embedded in the market-economy rationale of the neo-liberal project. The paper identifies a trend towards the ?equitisation? of pension funds as part of a broader process of marketisation of pensions as social right. The significance of the investment decision for pension occupational funds becomes crucial since funds are becoming major actors in the economic field. Their investment decision depends much on power relations between labour and capital ranging for example from social development (public houses, creation of jobs in the national environment) to the creation of profits through domestic and foreign financial markets. The paper concludes that pension occupational funds are re-embedded in a framework of choices, dominated increasingly more from the market economy rationale and the neo-liberal political project. ..PAT.-Unpublished Manuscript
Keywords: Germany; Great Britain; Sweden; capital; decision making; pensions; political economic analysis

Beyond the boycott: labor rights, human rights, and transnational activism - Seidman, G. (Russell Sage Foundation, 2007)
Keywords: business & economics - international; business & economics / business ethics; law / labor & employment; political science / human rights; political science / labor & industrial relations; political science / labour & industrial relations; social science - developing and emerging countries; social science / sociology / general

Redistribution and Markets in the Economy of Ancient Mesopotamia: Updating Polanyi - Silver, Morris (Antiguo Oriente, 2007)
Keywords: capital formation; damkar/tamkaru; demand/supply curve; equivalence; redistribution

Society Must Be Protected - Turner, Mandy (Journal of Corporate Citizenship, 2007)
The multiple ways in which multinational corporations, financial and commodity markets and global trade feed into today's civil wars have recently become a key policy concern of the international community. Over the past five years, a number of initiatives have been launched, aimed at controlling the trade in conflict goods, ensuring good resource governance, advocating corporate social responsibility and promoting conflict-sensitive business practices. This article assesses these initiatives through the lens of Karl Polanyi's conception of the 'double movement', i.e. that capitalism automatically provokes protectionist impulses. It assesses the spaces created by neoliberal globalisation for illicit economic activity and conflict entrepreneurs, the relationship between the economy and conflict, and initiatives aimed at reducing conflict 'triggers'. It concludes that, in addition to the tension between commodification and social protection, there is another tension at work: between those who call for tough mandatory policies and those who promote best-practice guidelines.
Keywords: Polanyi; business and conflict; capital market; commodification; corporate social responsibility; corruption; international business enterprises; international trade; protectionism; sanctions; social protection; social responsibility of business